Medical Image Protection Algorithm Based on Deoxyribonucleic Acid Chain of Dynamic Length - Xue, Xianglian; Jin, Haiyan; Zhou, Dongsheng; Zhou, Changjun (Frontiers in Genetics, 2021)
Current image encryption algorithms have various deficiencies in effectively protecting medical images with large storage capacity and high pixel correlation. This paper proposed a new image protection algorithm based on the deoxyribonucleic acid chain of dynamic length, which achieved image encryption by DNA dynamic coding, generation of DNA dynamic chain and dynamic operation of row chain and column chain. First, the original image is encoded dynamically according to the binary bit from a pixel, and the DNA sequence matrix is scrambled. Second, DNA sequence matrices are dynamically segmented into DNA chains of different lengths. After that, row and column deletion operation and transposition operation of DNA dynamic chain are carried out, respectively, which made DNA chain matrix double shuffle. Finally, the encrypted image is got after recombining DNA chains of different lengths. The proposed algorithm was tested on a list of medical images. Results showed that the proposed algorithm showed excellent security performance, and it is immune to noise attack, occlusion attack, and all common cryptographic attacks.